Intelligent Transport Systems, From Research and Development to the Market Uptake - Ferreira, J.; Martins, A.; Vitor Monteiro (2019)
This book constitutes the proceedings of the Second EAI International Conference on Intelligent Transport Systems, INTSYS 2108, which was held in Guimarães, Portugal, in November 2018. The 11 revised full papers were selected from 16 submissions and are organized in four thematic sessions on parking and collaborative approaches, case studies and simulation, mobility and planning, and Future 5V.